Alternative management strategies for growing and stocker cattle - Duncan, Zachary Michael (Kansas State University, 2024)
A series of experiments were conducted to evaluate alternative management strategies for limit-fed growing beef cattle and yearling stocker cattle. Previous research reported improvements in feed efficiency when growing cattle were limit-fed a high-energy diet based on corn and corn co-products compared with a traditional high-roughage diet fed for ad libitum intake; however, cattle feeders have voiced concerns that limit-feeding may increase bunk space requirements. In Exp. 1, 385 crossbreed steers were assigned to 1 of 4 bunk allotment treatments: 25.4, 38.1, 50.8, or 63.5 cm of bunk per calf and limit-fed a high-energy diet once daily for 58 d. Average daily gains (ADG) tended to respond quadratically (P = 0.10) and were greatest for calves allotted 50.8 cm of bunk per calf; however, final body weights (BW), dry matter (DM) intake, and gain-to-feed (G:F) did not differ (P ≥ 0.34) among treatments. In Exp. 2, almond hulls were evaluated as an alternative fiber source in limit-fed growing beef cattle diets. Three-hundred sixty-four steers and 8 ruminally cannulated heifers were fed 1 of 4 experimental diets. The control diet contained (DM basis) 39.5% dry-rolled corn, 7.5% supplement, 40% wet-corn gluten feed, and 13% prairie hay. Non-ground or ground almond hulls replaced prairie hay and were fed at 13% of diet DM or non-ground almond hulls were fed at 26% of diet DM and replaced 13% prairie hay and 13% dry-rolled corn. Replacing dry-rolled corn with almond hulls reduced growth performance, ruminal volatile fatty acid (VFA) concentrations, and ruminal ammonia concentrations; however, replacing prairie hay with almond hulls resulted in similar final BW, ADG, and apparent diet digestibility. Inclusion of wet distillers grains (WDGS) and wheat middlings (MIDDS) in growing and finishing diets have been evaluated; however, the effects of incorporating MIDDS into WDGS (i.e., WDGS+MIDDS) on apparent diet digestibility and ruminal fermentation characteristics are unknown. In Exp. 3, 4 ruminally cannulated crossbred heifers were fed a growing diet that contained WDGS or WDGS+MIDDS at 40% of diet DM. In addition, 4 ruminally cannulated Holstein steers were fed a finishing diet that contained WDGS or WDGS+MIDDS at 30% of diet DM. Inclusion of WDGS+MIDDS in a growing diet increased (P = 0.03) starch intake but did not influence (P ≥ 0.17) apparent DM digestibility, total VFA concentrations, or ruminal pH. When fed in a finshing diet, WDGS+MIDDS increased (P = 0.02) ruminal pH and caused minor shifts in individual ruminal VFA concentrations. In addition, inclusion of WDGS+MIDDS in both growing and finishing diets reduced ruminal ammonia concentrations. The Kansas Flint Hills represent the largest segment of the United States stocker cattle industry. Prescribed fires are traditionally applied in March and April to improve grazing cattle growth performance and native warm season grass production. Shifting prescribed fire timing from March-April to August-October may reduce basal cover of invasive plant species and subsequently improve native forb diversity; however, effects of applying fire later in the year on stocker cattle growth performance during the subsequent grazing season have not been extensively evaluated. During a six-year experiment, 18 pastures were grouped by watershed and each watershed was randomly assigned to 1 of 3 prescribed-fire treatments: spring (11 April ± 5.7 d), summer (25 August ± 6.2 d), or autumn (2 October ± 9.0 d). Over 5 consecutive grazing seasons, 1,939 yearling stocker calves were grazed from May to August and rangeland plant composition was measured annually in June. Average daily gains were greater (P = 0.02) for calves assigned to spring-burned pastures compared with calves assigned to summer- or autumn-burned pastures but did not differ (P ≥ 0.55) between calves grazing summer- or autumn-burned pastures. Basal cover of total graminoids and total forbs did not differ (P ≥ 0.30); however, prescribed-fire timing tended to influence basal cover of C3 (P = 0.06) and C4 (P = 0.08) grasses. Overall, these data demonstrate how alternative management strategies can influence growth performance of growing beef cattle or yearling stocker cattle. Cattle managers should evaluate the strengths and weaknesses of each alternative to determine how they best fit into their respective programs.
Keywords: Limit feeding; Bunk space; Almond hulls; Wet distillers grains; Wheat middlings; Prescribed-fire timing